Downregulation of IL-6 and TNF-α Expression with Mesenchymal Stem Cells Therapy in Allergic Rhinitis Rats Models - Restimulia, Lia; Dewi, Dian Andriani Ratna; Nazar, Mohammad Ariq; Irawan, Risky Chandra Satria; Ghaissani, Shabrina Syifa; Haryono, Erlina (Stem Cell and Cancer Research (SCCR), 2022)
Rhinitis is an inflammatory that characterized by nasal symptoms due to the condition of the nasal mucosa that trigerred by an interaction between environmental allergens and immunoglobulin (Ig)E. It is driven by host factors, infection, pathogens and various inflammatory pathways such as TNF-α that released in allergic responses from both mast cells and macrophages through IgE-dependent mechanisms. Secretome hypoxia mesenchymal stem cells (SH-MSCs) contain anti-inflammatory soluble molecules were able to improve the conditions of endothelial damage, inflammation and oxidative stress by decreasing levels of IL-6, TNF-α, ROS and increasing eNOS. This study will investigate the effect of SH-MSCs at a dose of 300 µL on TNF- and IL-6 expression in rat model ovalbumin-induced rhinitis in vivo. Thirty male Wistar rats were randomly divided into 3 groups: control, treatment and sham group that administrated through intramuscular injection. The results of this study found that SH-MSCs can downregulate the inflammatory cytokines TNF-α and IL-6 in rat model ovalbumin-induced rhinitis in vivo